Definition formation process of language learning strategy: Issues and development - Mat Teh, Kamarul Shukri (Issues in Language Studies, 2013)
Orientation of language learning strategy (LLS) research which was not based on solid theory in the early stages, and differences in second and foreign language learning setting have led to the formation of LLS terminologies and definition that are inconsistent and divergent. This situation has resulted in conflicting views among researchers. Hence, this paper attempts to identify issues and developments that occur in the process of defining LLS. It begins by discussing issues that have surfaced in the definition of LLS in terms of determining whether it is conscious or unconscious in nature. Debates pertaining to LLS definition have also been muddled with issues concerning the nature of learning strategy either as an action, or a mental activity or both. Some changes in the pattern of definitions that scholars created have been identified. These include the change in focus from product to process and the change in terms of the definitions’ comprehensiveness, among others. The influence of cognitive and social cognitive theories in defining LLS has also been observed after more than ten years of study in this field. As a result, this paper affirms that the main frame for the definition of LLS involves two components which are elements and purpose.